2015
DOI: 10.1136/vr.102862
|View full text |Cite
|
Sign up to set email alerts
|

Association between birth conditions and glucose and cortisol profiles of periparturient dairy cows and neonatal calves

Abstract: Parturition in cattle is a stressful event for both the dam and the offspring. Stress and pain can alter the energy profile of calves and calving cows, producing a metabolic imbalance at birth. This study aimed to assess the effects of dystocia and oxytocin and calcium infusion on metabolic homeostasis in dairy cows and calves. Thirty Holstein cows and their calves were divided into three groups: an eutocia group (n=10), in which no calving assistance was needed; a dystocia group, which required mild-to-severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
2
21
2
Order By: Relevance
“…In cattle, dystocia has been found to be related to several negative outcomes, such as survival of newborn calves (Eriksson et al, 2004;Bicalho et al, 2008;Barrier et al, 2013). This is so because dystocial calves normally experience higher physiological stress, acidosis and hypoxic state which result in lower vigor (Barrier et al, 2012;Kovács et al, 2016) and consequently in reduction in the transfer of passive immunity, as well as important metabolic changes (Barrier et al, 2013;Vannucchi et al, 2015). Stillborn calves from dystocic parturition not necessarily exhibit specific types of trauma, but do exhibit larger lesions than their eutocic counterparts, indicating that they experienced greater trauma during delivery (Barrier et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In cattle, dystocia has been found to be related to several negative outcomes, such as survival of newborn calves (Eriksson et al, 2004;Bicalho et al, 2008;Barrier et al, 2013). This is so because dystocial calves normally experience higher physiological stress, acidosis and hypoxic state which result in lower vigor (Barrier et al, 2012;Kovács et al, 2016) and consequently in reduction in the transfer of passive immunity, as well as important metabolic changes (Barrier et al, 2013;Vannucchi et al, 2015). Stillborn calves from dystocic parturition not necessarily exhibit specific types of trauma, but do exhibit larger lesions than their eutocic counterparts, indicating that they experienced greater trauma during delivery (Barrier et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The higher catecholamine production during prolonged calving may be responsible for the increased vascular flow to the brown adipose tissue, and, consequently, for increased heat production (Bellows and Lammoglia, 2000). The higher neonatal stress observed in dystocic calves (Vannucchi et al, 2015c) may corroborate this finding, favoring the organic response to adverse extrauterine conditions. Also, in this study, we observed that obstetric assistance favored thermal maintenance only in prolonged calving (>4 h).…”
Section: Abmentioning
confidence: 87%
“…Morbidity and mortality remain high during the neonatal period (from day 2 to day 28 of life) and then decline as calves develop and gain in body weight [3]. metabolic pathways during the transitional period from intra-uterine to extra-uterine life [13].…”
Section: Introductionmentioning
confidence: 99%